2018
DOI: 10.1021/acs.molpharmaceut.8b00764
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally Restricted, Highly Potent, Selective, Aqueous-Soluble EP2 Antagonist with Anti-Inflammatory Properties

Abstract: The prostaglandin E2 receptor, EP2, plays an important role in physiology and in a variety of pathological conditions. Studies indicate that EP2 is pro-inflammatory in chronic peripheral and central nervous system disease and cancer models. Thus, targeting the EP2 receptor with small molecules could be a therapeutic strategy for treating inflammatory diseases and cancer. We recently reported a novel class of competitive antagonists of the EP2 receptor. However earlier leads displayed low selectivity against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Prior to administering TG8-260 to animals, we investigated its in vitro inflammation modulating properties and found that TG8-260 reverses the change in expression of inflammatory mediators induced by the combination of LPS and EP2 activation, consistent with other EP2 receptor antagonists created in our laboratory [1,2,21,28,29]. Although IL-10 displays pleiotropic effects it is largely an anti-inflammatory mediator and therefore enhancing IL-10 expression will quell inflammation.…”
Section: Discussionsupporting
confidence: 55%
“…Prior to administering TG8-260 to animals, we investigated its in vitro inflammation modulating properties and found that TG8-260 reverses the change in expression of inflammatory mediators induced by the combination of LPS and EP2 activation, consistent with other EP2 receptor antagonists created in our laboratory [1,2,21,28,29]. Although IL-10 displays pleiotropic effects it is largely an anti-inflammatory mediator and therefore enhancing IL-10 expression will quell inflammation.…”
Section: Discussionsupporting
confidence: 55%
“…It could be predicted from the table that all of the eugenol based derivatives shown logP values within the limit. Lesser blood–brain barrier (BBB) access and poor membrane permeability is associated with a larger rate of tPSA (> 145 Å 2 ) [32]. Nearly all of the synthesized derivatives exhibited acceptable values of tPSA within a range of 35–140 (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, MDSCs expressed high levels of COX2 and were a major source of PGE2 secretion in human cancer (Obermajer et al, 2011). Hence, inhibition of PGE2 production using non-selective or COX2-selective blockers as well as selective antagonists of PGE2 receptors (Ganesh et al, 2018;Markovic et al, 2017) is likely to prevent MDSC-related MDR.…”
Section: Therapeutic Approaches Targeting Mdscsmentioning
confidence: 99%